Successful Management of a Ruptured Ovarian Pregnancy at 11 Weeks of Gestation : A Case Report - Chirag Sharma; Hina Patel (Dr. Annil Mahajan, 2024)
Ovarian pregnancy, an uncommon type of non-tubal ectopic pregnancy, typically results in rupture before the completion of the first trimester. The utilisation of intrauterine devices (IUDs) is a significant risk factor for this condition. Ovarian ectopic pregnancies, constituting 0.5% to 3.5% of all ectopic pregnancies, can pose a serious threat to life due to the potential for severe haemorrhaging upon rupture. This case involves a 38-year-old woman in her third pregnancy with a history of two live births at 11 weeks gestation who presented with abdominal pain. The diagnosis of ectopic pregnancy was established, and intra-operative and histopathological assessments confirmed it as an ovarian pregnancy. The patient underwent treatment with an ipsilateral salpingo-oophorectomy and a contralateral salpingectomy.